Límite de una sucesión con GeoGebra - Arias Balarezo, Ana Lucía (2021)
The objective of this workshop is to analyze how the GeoGebra software can be used in the teaching-learning of the dynamic conception of the concept of limit for students of the Unified General Baccalaureate, the theoretical support of it constitutes the APOE theory of Dubinsky in what which refers to the genetic decomposition of the concept oflimit of a function. This research is qualitative at an exploratory-descriptive level, both a documentary bibliographical research and a field research were used, for which an instrument composed of five didactic tasks was developed that has multiple choice and completion questions, presented on the platform. Geogebra.org. One of the main results that is expected to be achieved is a greater understanding of the concept of limit through the graphic representation system compared to the other representation systems.